The impact of paternalistic leadership on innovation and performance in chinese public hospitals - Tan Zhiying (2017)
Chinese public hospitals have their unique characteristics. CEOs of Chinese public hospitals face multiple difficulties and challenges, which influence the performance of public hospitals. Leadership is an essential variable to organizational effectiveness. Based on the Chinese culture context, paternalistic leadership featuring authoritarianism, benevolence, and moral leadership, is one of the popular leadership theories in Chinese businesses. Furthermore, innovation is an important contribution to organizational performance. The purpose of this study is to examine the relationship between paternalistic leadership, innovation and performance in Chinese public hospitals. The sample includes 103 CEOs from public hospitals in 11 Chinese provinces and the data collected using a survey. The research found that paternalistic leadership and innovation did not have significant positive impact on hospital performance. Paternalistic leadership had significant positive impact on innovation. Additionally, paternalistic leadership did not moderate the relationship between innovation and performance. Distinguishing the three elements of paternalistic leadership, moral leadership had the expected positive effects. Moral leadership was positively and significantly related to innovation and internal business processes of performance. Moreover, moral leadership and innovation were both negatively related to the financial performance and innovation is positively related to the learning and growth of performance. Overall, moral leadership of paternalistic leadership had the greatest impact for the public hospital CEOs. Therefore, these results emphasized the importance of moral leadership in Chinese public hospitals. This study has some limitations due to the use of only one questionnaire and the sample size in the study. Future studies may examine the relationship between paternalistic leadership, innovation and performance in other contexts.